Inorganic carbonized coating as well as preparation method and application thereof in sulfuric acid-resistant protection
By using inorganic carbonized coatings made of steel slag and petroleum coke slag, the problem of insufficient acid resistance in acidic environments is solved, and high bonding strength and good sulfuric acid corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411297145.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art has shortcomings in improving the acid resistance of concrete, especially in the problem of deterioration of bonding strength under large pore filling and ultraviolet irradiation.
An inorganic carbonized coating made of steel slag and petroleum coke slag is used to generate dense structure calcium carbonate and silica through carbonization, which improves bonding strength and acid resistance.
It achieves high bonding strength and good resistance to sulfuric acid corrosion, which can effectively prevent concrete from erosion in acidic environments.
Smart Images

Figure CN119842248A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sulfuric acid resistance protection, and specifically relates to an inorganic carbonized coating and a preparation method thereof and application in sulfuric acid resistance protection. Background Art
[0002] With the development of the fields of construction, engineering and infrastructure, concrete, as a common inorganic non-metallic material, is used in huge quantities. However, concrete materials themselves have certain defects. For example, after long-term use, they will produce defects such as expansion and cracking and falling off. Especially in acidic environments such as industrial wastewater and urban sewage, acidic liquids or gases contact concrete for a long time, which will cause chemical reactions inside the concrete, accelerate the deterioration of the concrete, and even expose and corrode the internal steel bars, causing the overall structure of the concrete to be destroyed, posing serious safety hazards and economic losses.
[0003] In order to prevent concrete from being damaged prematurely in an acidic environment and to improve the acid resistance of concrete, many studies have been conducted. For example, alkali-activated cementitious materials are used to increase the strength of concrete, improve the pore structure and pore size distribution, increase the acid resistance of concrete, and enhance the durability of concrete. Another method is to apply a coating on the surface of concrete, and use the density and acid and alkali resistance of the coating to isolate the concrete from the outside world, so that external ions and other harmful substances cannot come into contact with the concrete to react, thereby achieving a method of improving the durability of concrete.
[0004] At present, there are two types of research on coatings: one is organic coatings, such as epoxy resin, silicone or acrylic acid, which can improve the acid resistance of concrete to a certain extent, but also have certain defects, such as the deterioration of its bonding strength under ultraviolet radiation. The other is inorganic coatings, which have good acid resistance, such as inorganic silicates, which can form a film on the surface and penetrate into the concrete to produce chemical substances to fill the pores and resist ion erosion, but the hydration products generated by the reaction can only fill small pores, and large pores cannot be filled well, which is a defect. Summary of the invention
[0005] The purpose of the present invention is to provide an inorganic carbonized coating and a preparation method thereof and application in sulfuric acid resistance protection. The inorganic carbonized coating provided by the present invention has a dense structure, high bonding strength and good acid resistance.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides an inorganic carbonized coating, which is prepared from raw materials including the following substances in parts by weight:
[0008] 50-100 parts of steel slag, 0-50 parts of petroleum coke slag, water and a water reducing agent; the mass ratio of the total mass of the steel slag and the petroleum coke slag to the mass of water is 100:29-37; the mass ratio of the total mass of the steel slag and the petroleum coke slag to the mass of the water reducing agent is 100:0.5-1.
[0009] Preferably, the particle size of the steel slag is 1 to 100 microns.
[0010] Preferably, the particle size of the petroleum coke residue is 1 to 100 microns.
[0011] Preferably, the water reducer is a polycarboxylic acid high-efficiency water reducer.
[0012] Preferably, the thickness of the inorganic carbonized coating is 0.5 to 1.2 mm.
[0013] The present invention also provides a method for preparing the inorganic carbonized coating described in the above scheme, comprising the following steps:
[0014] Steel slag, petroleum coke slag, water and a water reducing agent are mixed to obtain a slurry, and then the slurry is coated on a substrate and carbonized after standing to obtain the inorganic carbonized coating on the substrate.
[0015] Preferably, the coating is performed by brushing; the thickness of the brushing is 0.6 to 1.0 mm.
[0016] Preferably, the standing time is 0.5 to 1.5 hours.
[0017] Preferably, the carbonization conditions are: CO2 concentration is 20-40%, humidity is 70-90%; the carbonization pressure is standard atmospheric pressure, the temperature is 25-40°C, and the insulation time is 16-24h.
[0018] The present invention also provides the use of the inorganic carbonized coating described in the above scheme or the inorganic carbonized coating obtained by the preparation method described in the above scheme in sulfuric acid resistance protection.
[0019] The present invention provides an inorganic carbonized coating. The present invention utilizes the abundant gelling active substances such as tricalcium silicate, dicalcium silicate and free calcium oxide in steel slag. The carbonization of steel slag will generate a large amount of substances such as calcium carbonate and silicon dioxide. These substances can form a dense structure, so that the inorganic carbonized coating has a high bonding strength, good sulfuric acid corrosion resistance, and good waterproof effect. In addition, petroleum coke slag has a high calcium content, which can supplement the calcium source and further promote the carbonization reaction process.
[0020] The present invention also provides a method for preparing the inorganic carbonized coating of the above scheme. The present invention uses solid wastes such as steel slag and petroleum coke slag as raw materials to realize the resource high value of solid wastes, which not only saves costs and has good economic benefits, but also plays a role in protecting the environment and has good ecological benefits.
[0021] The present invention also provides the use of the inorganic carbonized coating described in the above scheme or the inorganic carbonized coating obtained by the preparation method described in the above scheme in sulfuric acid resistance protection. The inorganic carbonized coating provided by the present invention has a dense structure, good resistance to sulfuric acid corrosion, and can effectively prevent the protected substrate from being corroded by sulfuric acid. Sulfur dioxide exists in the flue gas discharged from the seawater cooling tower. During the rising process, sulfur dioxide contacts with cold air to form a strong acid substance with a pH close to 0. The inorganic carbonized coating provided by the present invention has a good resistance to sulfuric acid corrosion and is particularly suitable for use in seawater cooling towers to improve the durability of concrete. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 This is a morphology diagram of the steel slag used in the present invention;
[0024] Figure 2 The XRD diagram of the steel slag used in the present invention;
[0025] Figure 3 This is a morphology diagram of the petroleum coke residue used in the present invention;
[0026] Figure 4 The XRD diagram of the petroleum coke residue used in the present invention;
[0027] Figure 5 A morphological diagram of the inorganic carbonized coating provided by the present invention;
[0028] Figure 6 It is a test chart of sulfuric acid resistance of the inorganic carbonized coating of Example 1 (a), Example 2 (b), Example 3 (c), Example 4 (d), Example 5 (e), Example 6 (f) and the control group (g) of the present invention. DETAILED DESCRIPTION
[0029] The present invention provides an inorganic carbonized coating, which is prepared from raw materials including the following substances in parts by weight:
[0030] 50-100 parts of steel slag, 0-50 parts of petroleum coke slag, water and a water reducing agent; the mass ratio of the total mass of the steel slag and the petroleum coke slag to the mass of water is 100:29-37; the mass ratio of the total mass of the steel slag and the petroleum coke slag to the mass of the water reducing agent is 100:0.5-1.
[0031] In parts by mass, the raw material of the inorganic carbide coating provided by the present invention includes 50 to 100 parts of steel slag, preferably 60 to 90 parts, more preferably 70 to 80 parts, and further preferably 75 parts.
[0032] In the present invention, the particle size of the steel slag is preferably 1 to 100 microns, more preferably 5 to 50 microns, further preferably 6 to 30 microns, and further preferably 8 to 10 microns.
[0033] In parts by mass, the raw materials of the inorganic carbonized coating provided by the present invention include 0 to 50 parts of petroleum coke slag, preferably 10 to 40 parts, more preferably 20 to 30 parts, and further preferably 25 parts.
[0034] In the present invention, the particle size of the petroleum coke residue is preferably 1 to 100 microns, more preferably 5 to 50 microns, further preferably 6 to 30 microns, and further preferably 8 to 10 microns.
[0035] The raw materials of the inorganic carbonized coating provided by the present invention include water; the water is preferably deionized water; the ratio of the total mass of the steel slag and petroleum coke slag to the mass of water is preferably 100:30-36, specifically 100:31, 100:32, 100:33, 100:34, 100:35 or 100:36.
[0036] The raw materials of the inorganic carbonized coating provided by the present invention include a water reducer; the ratio of the total mass of the steel slag and the petroleum coke slag to the mass of the water reducer is preferably 100:0.6-0.9, more preferably 100:0.7-0.8.
[0037] In the present invention, the water reducing agent is preferably a polycarboxylic acid high-efficiency water reducing agent. The present invention improves the fluidity of the slurry by using the water reducing agent.
[0038] The thickness of the inorganic carbonized coating provided by the present invention is preferably 0.5 to 1.2 mm, more preferably 0.6 to 1.0 mm, and further preferably 0.7 to 0.9 mm.
[0039] The present invention also provides a method for preparing the inorganic carbonized coating described in the above scheme, comprising the following steps:
[0040] Steel slag, petroleum coke slag, water and a water reducing agent are mixed to obtain a slurry, and then the slurry is coated on a substrate and carbonized after standing to obtain the inorganic carbonized coating on the substrate.
[0041] In the present invention, steel slag, petroleum coke residue, water and a water reducing agent are mixed (referred to as the first mixing) to obtain a slurry. In the present invention, the first mixing is preferably: steel slag and petroleum coke residue are mixed (referred to as mixing A) to obtain a premixed slurry, and then the premixed slurry is mixed with water and a water reducing agent (referred to as mixing B).
[0042] In the present invention, the mixing B is preferably stirring mixing; the rotation speed of the stirring mixing is preferably 50 to 80 rpm, more preferably 60 to 70 rpm, and the stirring time is preferably 5 to 10 min, more preferably 6 to 8 min.
[0043] After obtaining the slurry, the present invention applies the slurry on a substrate and carbonizes it after standing, thereby obtaining the inorganic carbonized coating on the substrate. In the present invention, the coating is preferably brushing; the thickness of the brushing is preferably 0.6 to 1.0 mm, more preferably 0.4 to 0.8 mm, further preferably 0.5 to 0.7 mm, and further preferably 0.6 mm.
[0044] In the present invention, the standing time is preferably 0.5 to 1.5 hours, more preferably 0.5 to 1.0 hours. The present invention allows the calcium silicate component in the raw material to undergo a preliminary hydration reaction with water by standing, so as to better perform carbonization.
[0045] In the present invention, the carbonization equipment is preferably a carbonization box; the carbonization conditions are preferably: CO2 concentration is 20-40%, more preferably 25-35%, humidity is 70-90%, more preferably 75-85%; the carbonization pressure is preferably standard atmospheric pressure, the temperature is preferably 25-40°C, more preferably 30-35°C, the insulation time is preferably 16-24h, more preferably 18-22h, and further preferably 20h.
[0046] The present invention also provides the use of the inorganic carbonized coating described in the above scheme or the inorganic carbonized coating obtained by the preparation method described in the above scheme in sulfuric acid resistance protection.
[0047] The inorganic carbonized coating provided by the invention has a compact structure, good sulfuric acid corrosion resistance, and can effectively prevent the protected substrate from being corroded by sulfuric acid.
[0048] Sulfur dioxide exists in the flue gas discharged from the seawater cooling tower. During the rising process, the sulfur dioxide contacts with the cold air to form a strong acid substance with a pH close to 0. The inorganic carbonized coating provided by the present invention has good resistance to sulfuric acid corrosion and is particularly suitable for use in seawater cooling towers to improve the durability of concrete.
[0049] In the present invention, when the inorganic carbonized coating provided by the present invention is applied to a seawater cooling tower, the inorganic carbonized coating can be coated on a concrete substrate.
[0050] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0051] Example
[0052] The preparation method of the inorganic protective coating in this embodiment has the following specific steps:
[0053] (1) According to the ratio in Table 1, weigh the steel slag (morphology as Figure 1 As shown, the XRD pattern is Figure 2 As shown), petroleum coke slag (morphology as Figure 3 As shown, the XRD pattern is Figure 4 As shown), deionized water and polycarboxylic acid high performance water reducing agent, the above raw materials are stirred and mixed, the mixing time is 5min, and the rotation speed is 50rpm to obtain a slurry.
[0054] (2) The slurry was evenly applied on the concrete test block with a thickness of 0.8 mm.
[0055] (3) Place the painted concrete specimens in a carbonization box for carbonization. The CO2 concentration is 20%, the humidity is 90%, the pressure is standard atmospheric pressure, the temperature is 25°C, and the carbonization time is 24 hours.
[0056] (4) After carbonization, an inorganic protective coating is obtained, the morphology of which is as follows Figure 5 shown.
[0057] Table 1 Raw material ratio table of Examples 1 to 6 (g)
[0058] Steel slag Petroleum coke residue water Water reducing agent Example 1 100 0 29 1 Example 2 90 10 29 1 Example 3 80 20 29 1 Example 4 70 30 29 1 Example 5 60 40 29 1 Example 6 50 50 29 1
[0059] The bonding strength and water absorption of the inorganic carbonized coatings prepared in Examples 1 to 6 were tested (with the test blocks without coating as the blank control group), wherein the water absorption test was carried out 24 hours after the concrete test blocks were coated with the inorganic carbonized coating. The results are shown in Table 2.
[0060] Table 2 Adhesion strength and water absorption of inorganic carbonized coatings of Examples 1 to 6
[0061] Bond strength Water absorption Example 1 2.315 3.9% Example 2 1.632 1.2% Example 3 1.559 1.4% Example 4 1.375 1.7% Example 5 1.124 1.2% Example 6 1.079 1.6% Blank control group - 7.4%
[0062] It can be seen from Table 2 that the inorganic carbonized coating provided by the present invention has good bonding strength with the substrate and a certain waterproof effect. This is because the calcium carbonate generated by carbonization of steel slag is closely combined with the substrate to produce a good transition layer, so it has a higher bonding strength.
[0063] The inorganic carbonized coatings prepared in Examples 1 to 6 of the present invention were tested for sulfuric acid resistance (with the concrete test blocks coated with epoxy coatings as the control group): After the concrete test blocks were coated with inorganic carbonized coatings according to Examples 1 to 6, they were immersed in a sulfuric acid solution with a mass concentration of 5% for 7 days to observe their changes. The results are as follows: Figure 6 As shown:
[0064] according to Figure 6It can be seen that the inorganic carbonized coating provided by the present invention has good sulfuric acid resistance, and no peeling, falling or bubbling occurs on the surface; while the epoxy resin coating in the control group has obvious bubbling.
[0065] It can be seen from the above embodiments that the inorganic carbonized coating provided by the present invention has a dense structure, high bonding strength, good resistance to sulfuric acid corrosion, and good waterproof effect.
[0066] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. An inorganic carbonized coating, characterized in that: Prepared from raw materials including the following substances in parts by weight: 50-100 parts of steel slag, 0-50 parts of petroleum coke slag, water and water reducing agent; The mass ratio of the total mass of the steel slag and petroleum coke slag to the mass of water is 100:29-37; The ratio of the total mass of the steel slag and the petroleum coke slag to the mass of the water reducing agent is 100:0.5-1.
2. The inorganic carbonized coating according to claim 1, characterized in that: The particle size of the steel slag is 1 to 100 microns.
3. The inorganic carbonized coating according to claim 1 or 2, characterized in that: The particle size of the petroleum coke residue is 1 to 100 microns.
4. The inorganic carbonized coating according to claim 1, characterized in that: The water reducer is a polycarboxylic acid high efficiency water reducer.
5. The inorganic carbonized coating according to claim 1 or 2, characterized in that: The thickness of the inorganic carbonized coating is 0.5-1.2 mm.
6. The method for preparing the inorganic carbonized coating according to any one of claims 1 to 5, characterized in that: The following steps are involved: Steel slag, petroleum coke slag, water and a water reducing agent are mixed to obtain a slurry, and then the slurry is coated on a substrate and carbonized after standing to obtain the inorganic carbonized coating on the substrate.
7. The preparation method according to claim 6, characterized in that: The coating is performed by brushing; the thickness of the brushing is 0.6-1.0 mm.
8. The preparation method according to claim 6, characterized in that: The standing time is 0.5 to 1.5 hours.
9. The preparation method according to any one of claims 6 to 8, characterized in that: The carbonization conditions are: CO2 concentration of 20-40%, humidity of 70-90%; the carbonization pressure is standard atmospheric pressure, the temperature is 25-40°C, and the insulation time is 16-24h.
10. Use of the inorganic carbonized coating according to any one of claims 1 to 5 or the inorganic carbonized coating obtained by the preparation method according to any one of claims 6 to 9 in sulfuric acid resistance protection.
Citation Information
Patent Citations
Ultrastrong weather-resistant anticorrosive waterproof multipurpose material as well as preparation method and application thereof
CN115785715A
Steel slag-based concrete carbon sequestration protective coating as well as preparation method and application thereof
CN116655336A
Low-cost and high-solid-carbon-content aerated concrete and preparation method thereof
CN117886583A
Inorganic anti-carbonization coating, preparation method and application thereof, and inorganic anti-carbonization coating
CN117924983A
Concrete reinforcing method and reinforced concrete
CN118561296A